2001
DOI: 10.1046/j.1523-1755.2001.00790.x
|View full text |Cite
|
Sign up to set email alerts
|

Long-term beneficial effect of ACE inhibition on diabetic nephropathy in normotensive type 1 diabetic patients

Abstract: The beneficial effect of captopril in arresting the rise in systemic blood pressure and albuminuria is long lasting. A loss in GFR is minimal in most patients with diabetic nephropathy if normotension is sustained by prospective treatment with ACE inhibitors or restored by implementation of other antihypertensive medications with the development of hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
46
1
3

Year Published

2003
2003
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(53 citation statements)
references
References 18 publications
3
46
1
3
Order By: Relevance
“…Further study showed that an ARB-losartan (10), irbesartan (9), or valsartan (8)-significantly decreased urinary albumin excretion in normotensive type 2 diabetes. Consistent with the data obtained by these studies performed in Western countries (8,9,20,21), the present study demonstrates that telmisartan treatment elicits renoprotective effects in Japanese normotensive type 2 diabetic patients with microalbuminuria. Since changes in UACR were not significantly correlated with changes in blood pressure in normotensive subjects (Fig.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Further study showed that an ARB-losartan (10), irbesartan (9), or valsartan (8)-significantly decreased urinary albumin excretion in normotensive type 2 diabetes. Consistent with the data obtained by these studies performed in Western countries (8,9,20,21), the present study demonstrates that telmisartan treatment elicits renoprotective effects in Japanese normotensive type 2 diabetic patients with microalbuminuria. Since changes in UACR were not significantly correlated with changes in blood pressure in normotensive subjects (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…The ACE-Inhibitor Trial to Lower Albuminuria in Normotensive Insulin-Dependent Subjects (ATLANTIS) study demonstrated that treatment with ramipril had no effect on glomerular filtration rate, but significantly decreased microalbuminuria in normotensive type 1 diabetic patients (20). Similarly, captopril significantly decreased albuminuria in normotensive type 1 diabetic patients with albuminuria > 300 mg/d (21). Further study showed that an ARB-losartan (10), irbesartan (9), or valsartan (8)-significantly decreased urinary albumin excretion in normotensive type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Whether ROS production in this model is persistent seems unlikely, because treatment with DMTU (6 h before and for only 1 wk after Adriamycin administration) partially prevents proteinuria, loss of HS, and heparanase overexpression at later stages. Treatment with an angiotensin-converting enzyme (ACE) inhibitor or AT1A ameliorates proteinuria in both human and experimental renal diseases, including AN, and provides renoprotection (21,(25)(26)(27)(28)(29)(30). Antiproteinuric treatment with AT1A in this study led to a partially restored glomerular HS expression.…”
Section: Discussionmentioning
confidence: 64%
“…Activation of the renin angiotensin system (RAS) is associated with progression of both diabetic and nondiabetic kidney disease (2). Numerous studies have demonstrated that RAS blockade lowers the rate of urinary albumin excretion (UAE) and retards decline of renal function in diabetes (3)(4)(5)(6)(7). This protective effect probably reflects both the hemodynamic and nonhemodynamic effects of ACE inhibitors and angiotensin II (Ang II) receptor blockers.…”
mentioning
confidence: 99%